Kewenangan Pemerintah Daerah dalam Perizinan Pertanahan dengan Berlakunya UU Cipta Kerja - I Kadek Suwartana; Ketut Kasta Arya Wijaya; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2022)
The enactment of Law No. 11 of 2020 concerning Job Creation experienced pro and con problems in social life, especially in the land sector. Multi-interpretation of regional authority in terms of licensing the land sector encourages the government as soon as possible to synergize existing regulations. The problems are: 1) What is the legal arrangement for permits related to land? and 2) What is the government's role in licensing in the land sector? The purpose of this research is to be able to find out the legal regulation of licensing related to land, and to know the role of the government in licensing in the land sector. The research method used is a normative research method. Regulations regarding land permits are broadly regulated in the main agrarian laws, namely Law Number 5 of 1960, and Law Number 23 of 2014 concerning Regional Governments regarding permits for land management in regions according to the autonomous system. The authority and role of the government in terms of licensing the land sector is also regulated through the law on spatial planning and location permit regulations.